Effect of nonpharmacological interventions on poststroke depression: a network meta-analysis - Li, Ying; Wang, Yuanyuan; Gao, Lei; Meng, Xiaohan; Deng, Qidan (Frontiers in Neurology, 2024)
Purpose To investigate the effects of nonpharmacological interventions (NPIs) on poststroke depression (PSD) in stroke patients. Methods Computer searches were conducted on the PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database (VIP), and Wanfang databases from their establishment to December 2023. The selection was made using the inclusion and exclusion criteria, and 40 articles were included to compare the effects of the 17 NPIs on patients with PSD. Results Forty studies involving seventeen interventions were included. The network findings indicated that compared with conventional therapy (COT), superior PSD improvement was observed for cognitive behavioral therapy (CBT) + acupoint acupuncture (CBTA) (mean difference [MD], −4.25; 95% CI, −5.85 to −2.65), team positive psychotherapy (MD, −4.05; 95% CI, −5.53 to −2.58), music therapy (MT) + positive psychological intervention (MD, −2.25; 95% CI, −3.65 to −0.85), CBT (MD, −1.52; 95% CI, −2.05 to −0.99), mindfulness-based stress reduction (MD, −1.14; 95% CI, −2.14 to −0.14), MT (MD, −0.95; 95% CI, −1.39 to −0.52), acupoint acupuncture + MT (AAMT) (MD, −0.69; 95% CI, −1.25 to −0.14). Furthermore, CBT (MD, −3.87; 95% CI, −4.57 to −3.17), AAMT (MD, −1.02; 95% CI, −1.41 to −0.62), acupressure + MT (MD, −0.91; 95% CI, −1.27 to −0.54), and narrative care + acupressure (MD, −0.74; 95% CI, −1.19 to −0.29) demonstrated superior Pittsburgh Sleep Quality Index (PSQI) improvement compared with COT. Conclusion Evidence from systematic reviews and meta-analyses suggests that CBTA improves depression in patients with PSD. Moreover, CBT improves sleep in these patients. Additional randomized controlled trials are required to further investigate the efficacy and mechanisms of these interventions.